The Bright Side of Hematopoiesis: Regulatory Roles of ARID3a/Bright in Human and Mouse Hematopoiesis - Ratliff, Michelle L.; Templeton, Troy D.; Ward, Julie M.; Webb, Carol F. (Frontiers in Immunology, 2014)
ARID3a/Bright is a DNA binding protein that was originally discovered for its ability to increase immunoglobulin transcription in antigen-activated B cells. It interacts with DNA as a dimer through its ARID, or A/T-rich interacting domain. In association with other proteins, ARID3a increased transcription of the immunoglobulin heavy chain and led to improved chromatin accessibility of the heavy chain enhancer. Constitutive expression of ARID3a in B lineage cells resulted in autoantibody production, suggesting its regulation is important. Abnormal ARID3a expression has also been associated with increased proliferative capacity and malignancy. Roles for ARID3a in addition to interactions with the immunoglobulin locus were suggested by transgenic and knockout mouse models. Over-expression of ARID3a resulted in skewing of mature B cell subsets and altered gene expression patterns of follicular B cells, whereas loss of function resulted in loss of B1 lineage B cells and defects in hematopoiesis. More recent studies showed that loss of ARID3a in adult somatic cells promoted developmental plasticity, alterations in gene expression patterns, and lineage fate decisions. Together, these data suggest new regulatory roles for ARID3a. The genes influenced by ARID3a are likely to play pivotal roles in lineage decisions, highlighting the importance of this understudied transcription factor.